Business Model and Product Life Cycle Techniques to Improve Marketing in Healthcare Units - Sayyad Liyakat, Kazi Kutubuddin (E-COMMERCE FOR FUTURE & TRENDS, 2023)
In the Indian health service’s attempts to implement a very involved and expensive eHealth initiative, judgment has generally refused to look beyond information and communications technologies. Therefore, the effective integration of planned communication and information technology options with various business components of the healthcare framework has largely been disregarded, while the established and out-of-date business strategy of the Indian healthcare programme continues to be extremely limited but is instead updated toward the greatly increased and widespread infiltration of communication and information technology into the healthcare setting. Such editorial attention to the conceptual model’s configuration and description enables the identification of the impending effects of industrialization on the health industry prototype and, ultimately, the formulation of a strategy for reshaping Slovenia’s original healthcare market prototype through the use of information and communication technologies. The analysis is centred on case study findings and structured questionnaires with notable experts from all sectors of the medical system who have a significant stake in the business model concept. According to the findings, a successful transition of the healthcare market prototype should consider a number of requirements from the health system, including a rethinking of how the key players in the business model operate and their relationships with one another as well as a retooling of organizational, structural, and technical elements in line with long-term corporate objectives.